Influence of conflicting prior information on action anticipation in soccer players: an ERP study - Ji, Qingchun; Zhou, Chenglin; Wang, Yingying (Frontiers in Behavioral Neuroscience, 2023)
Objective Prior probability information and visual kinematic information are essential for action anticipation in athletes. The aims of this study were to examine how conflicting prior information influences anticipatory judgment in athletes vs. non-athletes and to explore the underlying cognitive mechanisms. Methods The aim of Experiment 1 was to determine the moment when prior information influenced action anticipation in athletes vs. non-athletes. To that end, 17 semi-elite soccer goalkeepers and 18 non-athletes received prior information about the probability of the direction that a player on a video would kick a ball into the goal. Participants then anticipated the trajectory of the ball when the action of the player’s kick on the video was truncated at the moment the foot contacted the ball (time T) or one frame (T-1; 50 ms) or two frames (T-2; 100 ms) before the foot-ball contact. The aim of Experiment 2 was to elucidate the adaptive cognitive-motor behavior exhibited by highly trained soccer players at the moment when their anticipatory performance was most influenced by prior information. Experiment 2 included 27 different semi-elite soccer players with many years of experience as a goalkeeper and 27 different non-athletes. Participants anticipated the direction of the kick when the kinematic action of the kicker at the moment the anticipatory performance of the participants was most influenced by prior information (as determined in Experiment 1) was congruent, incongruent, or neutral. Action anticipation accuracy and response time were evaluated for both experiments, whereas event-related potential components N1, N2, and P3 were assessed only in Experiment 2. Results The results of Experiment 1 showed that anticipatory accuracy was significantly higher among athletes than non-athletes and that anticipatory accuracy with directional information given was significantly higher than that when no prior information was given or when prior information without directional information was given (p < 0.001) for both T-1 (p’s ≤ 0.034) and T-2 (p’s < 0.001) occlusion points. In Experiment 2 using those two video occlusion times, the amplitude of the N1 component, which reflects selective attention to stimulus properties, was significantly higher in athletes than in non-athletes (p < 0.001). The amplitude of the N2 component, which has been associated with conflict monitoring, for the incongruent condition was significantly higher than that for both neutral (p < 0.001) and congruent (p < 0.001) conditions in athletes. Non-athletes exhibited no significant N2 amplitude differences for any prior information condition. Conclusion Integrating prior information enhanced action anticipation in semi-elite soccer players, particularly 50 and 100 ms before the foot-ball contact. Semi-elite soccer players prioritized early selective attention and conflict monitoring of kinematic information, facilitating action anticipation using the prior information.